Mapping the Knowledge Evolution of Character Education in Islamic Religious Studies: A Bibliometric Analysis - Farida Asy'ari; Al-Amin Al-Amin; Abdul Rozak; Marsuni Marsuni; Muttaqin Muttaqin; Farida Asy'ari; Al-Amin; Abdul Rozak; Marsuni; Muttaqin; Ade Putra Hayat; Siti Fatimatus Zahro; Ade Putra Hayat; Siti Fatimatus Zahro (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study maps the development, intellectual structure, and thematic evolution of research on character education within Islamic Religious Studies using a bibliometric approach. A total of 157 Scopus-indexed documents published between 2015 and 2025 were analyzed. The dataset was processed using Bibliometrix/Biblioshiny in R and VOSviewer v.1.6.20 to examine publication growth, source distribution, influential documents, keyword co-occurrence, thematic mapping, and collaboration patterns. The findings show that research on Islamic education and character education has grown rapidly, with an annual growth rate of 40.51% and publications distributed across 88 sources. The field is strongly shaped by Southeast Asian scholarship, particularly Indonesia, while international collaboration remains relatively limited at 15.29%. The most frequent keywords include Islamic education, character education, Islamic religious education, Indonesia, higher education, religious moderation, and Islamic boarding school, indicating a concentration on value formation, institutional contexts, and moral-religious education. The thematic map suggests that education, character, and Indonesia function as central motor themes, whereas Islamic values, curriculum, and educational technology appear as more specialized or emerging areas. However, the absence of cited-reference metadata in the exported dataset limits the extent to which co-citation-based intellectual structures can be inferred. This study contributes a data-driven overview of the research landscape and identifies future directions for strengthening comparative, interdisciplinary, and internationally collaborative studies on character education in Islamic Religious Studies.